Pengaruh Kepemimpinan Servant terhadap Kinerja Karyawan Moderasi Kepribadian Karyawan di Kantor Gubernur Provinsi Riau - Damri; Mhd Delvianto (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to analyze the influence of servant leadership on employee performance with employee personality as a moderating variable in the Riau Province Governor's Office. In the context of local government, understanding the factors that affect employee performance is crucial for improving the effectiveness of public service delivery. The study adopts a quantitative approach with a cross-sectional design, involving 100 employees of the Riau Province Governor's Office as respondents. Data were collected through a structured questionnaire measuring perceptions of servant leadership, employee performance, and employee personality. Data analysis employed descriptive statistics, reliability tests, classical assumption tests, and moderated regression analysis. The results demonstrate that servant leadership has a significant positive effect on employee performance (β = 0.578, p < 0.001). Furthermore, employee personality was found to significantly moderate the relationship between servant leadership and employee performance (β interaction = 0.132, p < 0.05). The research model explains 61.1% of the variance in employee performance (R² = 0.611). These findings underscore the importance of implementing servant leadership style in enhancing employee performance within the local government environment, while considering employee personality characteristics.